Rheological and Mechanical Layering of the Crust Underneath Thumbprint Terrains in Arcadia Planitia, Mars. Issue 11 (10th November 2021) - De Toffoli, B.; Massironi, M.; Mazzarini, F.; Bistacchi, A.
Abstract: In the area of Arcadia Planitia in the Northern hemisphere of Mars, mounds indicating fluid and sediment emissions have been already recognized. Here, we show that through fractal and fracture‐spacing analyses of a large vent population it is possible to infer the mechanical layering of the underlying subsurface. Our work includes the mapping of an entire population of 9, 028 vents over an area of 122, 000 km 2 . The analysis of mound distribution at the surface led to the formulation of inferences about the subsurface feeding conduits, and to the identification of three mechanical discontinuities at c. 4–5, c. 14–23, and c. 50–55 km. This evidence matches the mechanical stratigraphy recorded by the InSight NASA mission, and is in agreement with independent previous subsurface global modeling, supporting our conclusions. Plain Language Summary: The Martian northern hemisphere displays mounds interpreted to be the result of sediment and water erupting onto the surface. We analyzed the mounds spatial distribution and found patterns that reflects the extent at depth of the subsurface conduits that fed those mounds (array of fractures, i.e., high permeability pathways) allowing the sediment and water upwelling. These conduits thus connect the surface to the source of the erupted materials at depth. These source levels are located at the base of layers characterized by mechanical properties different from the adjacent ones (e.g., loose sediments vs. crystalline bedrock). Such layers are hence referred as mechanical discontinuities. We identified three discontinuities: at c. 4–5, c. 14–23, and c. 50–55 km. Our outcomes match the mechanical stratigraphy recorded by the InSight NASA mission, and is in agreement with independent previous subsurface global modeling, supporting our conclusions. Key Points: We present a complete mapping of a large vent population in the Arcadia Planitia region of the northern plains of Mars We reconstructed the subsurface mechanical layering underlying the vent field using spatial distribution analysis These analyses proved to be efficient and open the possibility of collecting subsurface rheological data from areas beyond InSight reach